Engaging Teens and Parents in Collaborative Practice: Perspectives on Diabetes Self-Management. (March 2014) - Sullivan-Bolyai, Susan; Bova, Carol; Johnson, Kimberly; Cullen, Karen; Jaffarian, Carol; Quinn, Diane; Aroke, Edwin N.; Crawford, Sybil; Lee, Mary M.; Gupta, Olga
Purpose: The purpose of this exploratory focus group study was to describe the perspectives of teens and their parents about self-management knowledge, behaviors (including division of labor associated with T1D management), and resources used to manage T1D. The overall goal is to use this information to develop a teen–family transition clinic. Methods: The self and family management behaviors framework undergirded the separate teen–parent focus groups that were conducted concurrently. Note-based qualitative content analysis was used, resulting in several important messages. Results: From the teens' perspective there was variation in interest in learning more about T1D and management. Those teens who had been diagnosed at a very young age reported not knowing anything else but diabetes, while those diagnosed later developmentally embraced the active learning process. Diabetes camp and peer group support were not seen as beneficial. All the teens were interested in "helping others" with diabetes. Parents shared the common struggle with transition of self-management, with variation in parenting styles. A small group of parents reported their "job" as a parent was to make sure their child was self-sufficient in self-management, but felt pressure from the health care providers (HCPs) to physically do the care, defeating the purpose. Parents and teens reported wanting HCPs to be less focused on "numbers" (blood glucose levels) and more on the whole person. Scheduling appointment changes and long waiting times were reported as problematic by all participants. Conclusions: Teen and parent perspectives are critical in designing future well-received adolescent–family transition clinics. Development from the ground up with family recommendations may contribute to high-quality health outcomes.